2017
DOI: 10.1016/j.eurpolymj.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Isotactic degradable polyesters derived from O-carboxyanhydrides of l-lactic and l-malic acid using a single organocatalyst/initiator system

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The use of acid/base crystalline adducts of mandelic acid and pyridine for the ROP of d - 3 could suppress the racemization, and thereby (Figure 2B) could produce highly stereoregular isotactic polymers up to 48.0 kDa (over 80 h with Ð * of 1.17), which display enhanced thermal properties compared with the atactic poly( 3 ) (Buchard et al, 2014). Similarly, the adducts of 4-methoxypyridine with l -lactic acid and β-benzyl α- l -malate could also initiate ROP of l - 1 minimized epimerization of α-protons; however, those adducts failed to provide isotactic poly( l - 4 ) (Bexis et al, 2017). Note that at low [OCA]/[initiator] ratios, epimerization still occurred in both polymers when using the acid-base adducts, suggesting that the pyridine adduct can still lead to epimerization even with decreased basicity (Bexis et al, 2017).…”
Section: Organocatalyst For Oca Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of acid/base crystalline adducts of mandelic acid and pyridine for the ROP of d - 3 could suppress the racemization, and thereby (Figure 2B) could produce highly stereoregular isotactic polymers up to 48.0 kDa (over 80 h with Ð * of 1.17), which display enhanced thermal properties compared with the atactic poly( 3 ) (Buchard et al, 2014). Similarly, the adducts of 4-methoxypyridine with l -lactic acid and β-benzyl α- l -malate could also initiate ROP of l - 1 minimized epimerization of α-protons; however, those adducts failed to provide isotactic poly( l - 4 ) (Bexis et al, 2017). Note that at low [OCA]/[initiator] ratios, epimerization still occurred in both polymers when using the acid-base adducts, suggesting that the pyridine adduct can still lead to epimerization even with decreased basicity (Bexis et al, 2017).…”
Section: Organocatalyst For Oca Polymerizationmentioning
confidence: 99%
“…Similarly, the adducts of 4-methoxypyridine with l -lactic acid and β-benzyl α- l -malate could also initiate ROP of l - 1 minimized epimerization of α-protons; however, those adducts failed to provide isotactic poly( l - 4 ) (Bexis et al, 2017). Note that at low [OCA]/[initiator] ratios, epimerization still occurred in both polymers when using the acid-base adducts, suggesting that the pyridine adduct can still lead to epimerization even with decreased basicity (Bexis et al, 2017).…”
Section: Organocatalyst For Oca Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 48 ] In 2014, Buchard and coworkers demonstrated that the application of acid/base ion pairs (crystalline adducts of mandelic acid and pyridine) as catalysts ( Figure ) for the polymerizaiton of enantiopure OCA derived from mandelic acid ( D ‐2) suppressed the epimerization, and delivered highly isotactic polyesters, which show improved performances compared with the atactic poly(2). [ 46 ] Similarly, the adducts of 4‐methoxypyridine with L‐lactic acid and β‐benzyl α‐ L ‐malate could also initiate polymerization of L ‐5 with minimized racemization; [ 55 ] however, those adducts could not offer isotactic poly( L ‐2). At low [OCA]/[initiator] ratios, racemization still existed when applying the acid/base adducts, indicating that the acid/base adducts can still result in racemization even with decreased basicity.…”
Section: Ring‐opening Polymerization Catalyzed By Acid/base Adductsmentioning
confidence: 99%
“…For a living polymerization process, O -carboxyanhydride of mandelic acid (manOCA) and mandelide (a cyclic diester of mandelic acid) are two primary-type monomers (Figure A). However, these two types of monomers of mandelic acid are easily racemized/epimerized during the polymerization process because of the slightly strong acidity of methine in mandelic acid. ,, The monomer of manOCA can be facilely synthesized, which is more active than mandelide for the ring-opening polymerization (ROP) under mild conditions; thus, much effort has recently been devoted to controlling the stereostructure of PMA in the ROP of manOCAs (Figure B). ,, Two organic catalytic systems of pyridine/acid adducts reported by Carbery and Davidson and thiourea–amine organocatalysts reported by Tao and Wang showed good stereostructure control for the ROP of manOCAs (Figure B). Because metal complexes usually are more active and easily modified via changing the ligands for the potentially stereoselective ROP of varied OCAs, , several metal complexes, for example, BDI–Zn complexes reported by Tong and Cheng, and bistrimethylsilylamide Zn/La reported by Xu, were also reported for the stereocontrolled ROP of manOCAs.…”
Section: Introductionmentioning
confidence: 99%